Perancangan Sistem Informasi Kasir Dengan Barcode Berbasis Web Dan Framework Codeigniter - Intan Julia (Jurnal Informatika, 2022)
In the development of information technology business is what the world needs without exception for Indonesia. In all fields, IT has used IT to process the ease of business activities. Of course, IT is applied in the company to create wider market opportunities so that the company products get closer to consumers. The purpose of the research on the Information System for drug promotion media is to make it easy for the public / Android users to find out some classifications of drugs, to promote drugs to the public that are available in Kimia Farma Pharmacy which is based on Android.